MEMAHAMI NILAI ETIKA DAN MORAL DONASI ORGAN - Bintoro, Ady (Jurnal Orientasi Baru, 2016)
Organ donation or Organ transplants cannot legitimate acts that are in themselves contrary to the dignity of persons and to the moral law. Organ donation or Organ transplants is not morally legitimate if it exposes the subject's life or physical and psychological integrity to disproportionate or avoidable risks. That actions does not conform to the dignity of the person if it takes place without the informed consent of the subject or those who legitimately speak for him.